2012
DOI: 10.1111/j.1600-0501.2012.02507.x
|View full text |Cite
|
Sign up to set email alerts
|

Early‐stage osseointegration capability of a submicrofeatured titanium surface created by microroughening and anodic oxidation

Abstract: This study demonstrates that a submicrofeatured titanium surface created by a combination of sandblasting and anodic oxidation enhances the strength of early-stage osseointegration, primarily because of the increased resistance of peri-implant bone tissue against external force rather than modulation of bone morphogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
(113 reference statements)
0
19
0
Order By: Relevance
“…The biological and physicochemical performances of this type of HA-coated and anodic oxidized implants for acquirement and stability of osseointegration were well described in the previous animal studies [21,33]. Biomechanical strength on cylindrical implants with the same HA surface was 1.8 times higher than on titanium implants with conventional sandblasted surface alone in rat femur model [21].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The biological and physicochemical performances of this type of HA-coated and anodic oxidized implants for acquirement and stability of osseointegration were well described in the previous animal studies [21,33]. Biomechanical strength on cylindrical implants with the same HA surface was 1.8 times higher than on titanium implants with conventional sandblasted surface alone in rat femur model [21].…”
Section: Discussionmentioning
confidence: 74%
“…Over 90% of bone-implant contact ratio (BIC) with little soft tissue intervention was observed on the HA implants in contrast with approximately 40% BIC and soft tissue intervention on sandblasted surface. In contrast, titanium implants with the same anodic oxidization on sandblasted surface increased neither BIC nor biomechanical strength as compared to sandblasted surface alone in the same experimental model despite slight enhancement in mineralization in bone-implant interface at early healing stage [33]. This HAcoating was carried out with flame spray and low-temperature calcination method which provides a drastic alteration in surface morphology on sandblasted titanium substrate as shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that increased surface hydrophilicity increases the likelihood of cell adhesion to the surface [46,47]. So, it results that surface chemistry is the dominant parameter governing surface properties [48]. This suggests that implant surface could be conditioned by different procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that titanium alloy implants treated with anodic oxidation created in the same procedure as that used in the present study had the capacity for earlier osseointegration 23) . The phosphoric acid remaining on the surface may affect the capacity for early bone-anodic titanium integration.…”
Section: Discussionmentioning
confidence: 56%
“…It was reported that a micro-rough surface Ti6Al4V alloy produced by anodic treatment enhanced active bone formation and stable fixation in bone tissue 22) . It was recently demonstrated that anodic oxidation of a sandblasted titanium surface enhanced the strength of early-stage osseointegration 23) . The advantages of anodic oxidation-created titanium nanostructures include the protein retention capability, which can be used in strategies for implant-mediated protein delivery 18) .…”
Section: Introductionmentioning
confidence: 99%